Innovation Platforms to Enhance Participation in Rainwater Management: Lessons from The Nile Basin Development Challenge with a Particular Focus on Political Economy and Equity Issues - Tucker, Josephine; Cullen, Beth; Amsalu, Aklilu; Ludi, Eva (2014)
This paper draws lessons from two years of work with ‘innovation platforms’ that were established by the Nile Basin Development Challenge (NBDC) program in an attempt to strengthen landscape-level rainwater management in Ethiopia. The NDBC’s work included the use of an innovation fund to support pilot interventions. This paper particularly reviews questions of political economy and equity in platform activities and examines decision-making processes, the roles and level of influence of different platform members, the nature of platform-community relations and the extent to which different groups are benefiting. The information presented in this working paper was gathered from a mixture of sources: interviews conducted with platform members; observation of meetings and activities by NBDC staff; official minutes of platform meetings and other associated events (e.g., training sessions) and informal discussions between NBDC staff and platform members.